Possible Mechanisms Underlying the Effects of Glucagon-Like Peptide-1 Receptor Agonist on Cocaine Use Disorder - Zhu, Changliang; Li, Hailiang; Kong, Xuerui; Wang, Yezhong; Sun, Tao; Wang, Feng (Frontiers in Pharmacology, 2022)
Cocaine use disorder (CUD) is a major public health challenge with a high relapse rate and lack of effective pharmacotherapies; therefore, there is a substantial need to identify novel medications to treat this epidemic. Since the advent of glucagon-like peptide-1 (GLP-1) receptors (GLP-1Rs) agonists (GLP-1RAs), their potential has been extensively explored and expanded. In this review, we first summarized the biological effects of GLP-1, GLP-1Rs, and GLP-1RAs. Subsequently, the recent literature examining the behavioral effects and the possible pharmacological mechanisms of GLP-1RAs on CUD was reviewed. Increasing preclinical evidence suggests that GLP-1RAs are promising in regulating dopamine release, dopamine transporter (DAT) surface expression and function, mesolimbic reward system and GABAergic neurons, and maladaptive behaviors in animal models of self-administration and conditioned place preference. In addition, the emerging role of GLP-1RAs in inhibiting inflammatory cytokines was reported. These findings indicate that GLP-1RAs perform essential functions in the modulation of cocaine-seeking and cocaine-taking behaviors likely through multifaceted mechanisms. Although the current preclinical evidence provides convincing evidence to support GLP-1RA as a promising pharmacotherapy for CUD, other questions concerning clinical availability, impact and specific mechanisms remain to be addressed in further studies.